Research on Topology Reconfiguration in Cognitive Radio Networks - Qian He (Dianxin kexue)
Considering the inevitable trends for heterogeneous network convergence and self-adaptation ability，cognitive radio network（CRN）concept has been proposed with some essential characteristics to achieve global endto-end goals.CRN are composed of cognitive devices which have the capable of changing network configurations based on the dynamic environment.This capability opens up the possibility of designing flexible and dynamic topology control strategies with the purpose of opportunistically reusing idle licensed spectrum and effectively achieving data transmission.This work focuses on the problem of designing effective topology reconfiguration algorithm to offer optimal routing solutions.